2006
DOI: 10.1002/anie.200502071
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Naturally Occurring Polyynes

Abstract: Over the past fifty years, hundreds of polyyne compounds have been isolated from nature. These often unstable molecules are found in sources as common as garden vegetables and as obscure as bacterial cultures. Naturally occurring polyynes feature a wide range of structural diversity and display an equally broad array of biological properties. Early synthetic efforts relied primarily on Cu-catalyzed, oxidative acetylenic homo- and heterocoupling reactions to assemble the polyyne framework. The past 25 years, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
204
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(206 citation statements)
references
References 208 publications
(203 reference statements)
1
204
0
1
Order By: Relevance
“…Polyynes, namely polyacetylenes, have been found in many food and dietary plants [1][2][3][4][5]. To date, pharmacological investigations have revealed that polyynes from natural sources show antibacterial, anti-fungal, antiinflammatory, nerotoxic and anticancer activities [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Polyynes, namely polyacetylenes, have been found in many food and dietary plants [1][2][3][4][5]. To date, pharmacological investigations have revealed that polyynes from natural sources show antibacterial, anti-fungal, antiinflammatory, nerotoxic and anticancer activities [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…) À C(sp) Cross-Coupling Reactions between 1,3-and 1,4-Substituted Cyclohexylzinc Reagents and Bromoalkynes through Remote Stereocontrol** Tobias Thaler, Li-Na Guo, Peter Mayer, and Paul Knochel* Alkynes are found in a vast array of natural products and bioactive molecules, [1] and make up important constituents in many functional materials, [1c, 2] including liquid crystals, [3] dyes, [4] and organic light-emitting diodes (OLEDs). [5] Therefore, the development of novel methods that allow an efficient and stereoselective introduction of the alkynyl unit into organic molecules is highly desirable.…”
mentioning
confidence: 99%
“…The challenging chemistry and variety of potent biological activities of polyacetylenic fatty acids, which includes activities against cancer cells, infecting microbes and plant alleopathy [12][13][14][15][16][17][18][19][20] , have excited interest among natural-product prospectors and bioactive discovery programmes, and have propelled our interest in new molecular structures and biosynthetic origins. In this report, we describe a three-gene pathway isolated from the Australian soldier beetle C. lugubris, leading to an 18-carbon precursor of DHMA, and the first eukaryote biosynthesis of conjugated polyacetylenic compounds.…”
mentioning
confidence: 99%